Achievements of Economic Progress the Industry Sector and Employment Challenges in Kabupaten Gresik - Ramadan, Putri Wulan; Setiawati, Ririt Iriani Sri (MediaTrend, 2024)
Gresik as an industrial area is spread based on the projection of the East Java Industrial Growth Center Master Plan. The growth of the industrial sector in Gresik as an economic opportunity is followed by wage progress in 2017-2021. With this, the economic projection in Gresik is very large which leads to escalation. However, there are employment challenges, namely the high unemployment rate in Gresik. So this study finds out how the growth of the manufacturing sector, labor force, and minimum wage affect the open unemployment rate. The research method uses a quantitative approach in classical assumption testing, model testing, multiple linear regression analysis, and hypothesis testing. The result of this study is that the growth of the manufacturing sector does not have a significant effect on the unemployment rate because the industrial scheme in Gresik is capital-intensive. Then the growth of the labor force has no significant effect on the unemployment rate because the unemployment factor is also seen from education. The growth of minimum wage has a significant and negative effect on the unemployment rate which reflects that wage can increase labor demand in Gresik. This research provides recommendations to the government on regional development policies to be able to create a multiplier effect for the economic sector and promise employment. The limitations of this study refer to the independent variables of the study so that future researchers can add several variables such as the level of education, inflation, and economic growth to create an update on the continuity of research issues that are in line.